The Role of Blockholder Ownership in Corporate Decisions. - Koperunthevy, K.; Vijayarani, K. (Kaveripakkam College of Arts and Science, India., 2012)
Corporate Governance ensures how the powers are distributed among different participant of a company. Blockholder ownership is also one kind of power distribution among shareholders. Blockholders are investors who have block equity shares of a company. This kind of ownership is motivated by share benefits of control and private benefits of control. These two control mechanism will lead to influence on corporate decisions. The block owners concentrate three major areas for decisions such as agency problem, financing activity and investing activity. Theoretically blockholders may try to reduce the agency problem and implement different compensation to managers. Also, financing decisions and investing decisions will be concentrated by blockholders based on the nature and conditions of a particular company’s financial position to maximize the value. Therefore, this study concentrates these three decisions areas.